THE SIGNIFICANCE OF ARTERIAL WALL STIFFNESS ASSESSMENT FOR METABOLIC SYNDROME - M. A. Druzhilov; O. Yu. Druzhilova; V. V. Otmakhov; T. Yu. Kuznetsova (Российский кардиологический журнал)
Aim. To evaluate the usefulness of the pulse wave velocity parameter (PWV) in aorta as an additional prognostic criteria for target organs damage and hence higher cardiovascular risk (CVR) in patients with metabolic syndrome (MS).Material and methods. Totally 74 normotensive asymptomatic for cardiovascular disorders patients studied, with MS, low and intermediate risk by SCORE (77,0% males, mean age — 45,1±5,0 y.). We performed the assessment of lipid profile, glucose profile, glomerular filtration rate, microalbuminuria (MAU), performed triplex brachiocephal arteries scanning, echocardiography, bifunctional 24-hour monitoring of blood pressure with PWV measurement in aorta. The value of PWV in aorta taken ≥7,9 m/s corresponds with carotid-femoral PWV >10 m/s and in this study it has been used as the criteria of early vascular ageing (EVA) for the selected age diapason of patients.Results. Higher values of PWV in aorta had patients with MAU (8,5±0,3 m/s vs. 7,6±0,7 m/s, р<0,001), carotid atherosclerosis (8,4±0,3 m/s vs 7,6±0,7 m/s, р<0,001), hypertrophy of carotid arteries wall (CA) (7,9±0,6 m/s vs. 7,5±0,7 m/s, р<0,05), left ventricle diastolic dysfunction (DD LV) (8,3±0,6 m/s vs. 7,6±0,6 m/s, р<0,01). The participants with MS and aortic PWV ≥7,9 m/s had significantly more prevalent carotid atherosclerosis (36,4% vs. 16,2%, р<0,05) and DD LV (33,3% vs. 16,2%, р<0,05). The usage of the value of aortic PWV ≥7,9 m/s made it to select among the patients with MS 100% persons with subclinical carotid atherosclerosis and MAU, 91,7% participants with DD LV, 66,7% persons with carotid arteries wall hypertrophy.Conclusion. It is aimful, to the patients with MS and low or moderate SCORE risk in case of the PWV at the level for EVA criteria, to perform screening of organ damage, firstly, subclinical atherosclerosis, for consequent reclassification of EVA and reconsideration of the volume of necessary prevention procedures.